2002
DOI: 10.1001/archpedi.156.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Rehospitalization for Neonatal Dehydration

Abstract: In this population with good access to medical care, serious sequelae of neonatal dehydration are rare. Interventions to decrease the frequency of neonatal dehydration should focus on first-time mothers and those who breastfeed exclusively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 27 publications
2
61
2
2
Order By: Relevance
“…If weight controls are missing or are only performed sporadically, there is a danger of making the diagnosis too late, with the necessity for rehospitalisation and the risk of neurological, vascular and other complications [6,23,25]. In our study population, babies with severe hypertonic dehydration showed only a few, non-specific clinical features, such as hypotension and increased fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…If weight controls are missing or are only performed sporadically, there is a danger of making the diagnosis too late, with the necessity for rehospitalisation and the risk of neurological, vascular and other complications [6,23,25]. In our study population, babies with severe hypertonic dehydration showed only a few, non-specific clinical features, such as hypotension and increased fatigue.…”
Section: Discussionmentioning
confidence: 85%
“…We studied a cohort from the Northern California Kaiser Permanente Medical Care Program (KPMCP), a mature managed care organization with integrated information systems. (6,(16)(17)(18)(19)(20) Given the pathophysiology of dehydration, which does not appear to affect any one particular part of the brain, we did not expect to find discrete neurological deficits among our cohort. We expected to find non-specific neurodevelopmental problems affecting multiple domains (i.e., decreases in performance across multiple areas measured).…”
mentioning
confidence: 86%
“…We identified subjects born in 1995-96 in previous nested-case-control studies. (6,19,21) Study participants were drawn from 1995-98 KPMCP live births (N=106,627) with birth weights of at least 2000 grams and gestational age of at least 36 weeks (1995-96 cohorts) or 34 weeks (1997-98 cohorts). Eligible subjects had to meet the dehydration definition given below (cases) or were randomly selected from the 1995-96 and 1997-98 birth cohorts (controls) (Figure).…”
mentioning
confidence: 99%
“…4 Compared with term neonates, late preterm neonates are at higher risk for hospital readmissions, post-neonatal mortality, sudden infant death syndrome, white matter injury, and neuro-developmental problems well into the school age years. [5][6][7][8] Nitric oxide (NO) is the product of a fiveelectron oxidation of L-arginine mediated by one of three NO synthases: endothelial, neuronal, and inducible NO synthases (eNOS, nNOS and iNOS). 9 Neuronal NOS and eNOS are responsible for the continuous basal release of NO.…”
Section: Advances In Knowledgementioning
confidence: 99%